Analysis of Online Customer Loyalty Travel Agents in Jakarta: How do Social Media Marketing, Customer Relationship Management, and Customer Value Play a Role? - Wulandari, Pratiwi; Suhud, Usep; Febrilia, Ika (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze how social media marketing, customer relationship management, and customer value contribute to customer loyalty and their impact on customer satisfaction. Using a quantitative approach, data was collected through questionnaires from 226 respondents who are users of online travel agent services Traveloka in Jakarta. The data analysis technique employed is Structural Equation Modeling (SEM) with the assistance of AMOS and SPSS software. The study results reveal that social media marketing strategies and customer relationship management play a significant role in enhancing customer loyalty as well as their satisfaction. Additionally, customer value is also proven to be a crucial factor in strengthening customer loyalty, which ultimately contributes to increased customer satisfaction. These findings emphasize that effective digital marketing, strong customer engagement, and providing added value can foster customer loyalty, which in turn positively impacts their satisfaction in using online travel agent services.